Предмет: Математика,
автор: novikovaartem2
a) (b + c)(b-c);
B) (n - m)(m + n);
6) (.3 - 7)(x + 7);
r) (y + 5)(5 - y);
Ответы
Автор ответа:
1
Ответ:
Пошаговое объяснение:
применим формулу a^2-b^2=(a+b)*(a-b)
a). b^2-c^2
в) (n-m)*(n+m)=n^2-m^2
б).x^2-7^2=x^2-49
г). (5+y)*(5-y)=25-y^2
Похожие вопросы
Предмет: Математика,
автор: Imatkovskaya
Предмет: Обществознание,
автор: lisichka12
Предмет: Алгебра,
автор: vikanika19971
Предмет: Математика,
автор: supermosyagina
Предмет: Обществознание,
автор: уеее1